2018
DOI: 10.3390/min9010003
|View full text |Cite
|
Sign up to set email alerts
|

Rare Earth Elements and Other Critical Metals in Deep Seabed Mineral Deposits: Composition and Implications for Resource Potential

Abstract: The critical metal contents of four types of seabed mineral resources, including a deep-sea sediment deposit, are evaluated as potential rare earth element (REE) resources. The deep-sea resources have relatively low total rare earth oxide (TREO) contents, a narrow range of TREO grades (0.049-0.185%), and show characteristics that are consistent with those of land-based ion adsorption REE deposits. The relative REO distributions of the deep-seabed resources are also consistent with those of ion adsorption REE d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…According to [10], who analyzed 2000 seafloor sediment samples at 78 Pacific sites, deep-sea muds show high concentrations of REE (2230 ppm maximum), and could constitute a potential source of these elements in the future. Such high REE concentrations in sediments were not confirmed either by the studies of [21], who studied samples from the central North Pacific, or [16], who examined material collected from the southern part of the Korean claim area (KORDI) of the Clarion-Clipperton Fracture Zone (CCFZ). The former research has shown that total REE contents vary from 418 ppm to 810 ppm, with an average of 532 ppm, while the latter recorded a range from 115 ppm to 1115 ppm, with an even lower average of 490 ppm.…”
Section: Ree In Deep-sea Sedimentsmentioning
confidence: 95%
See 1 more Smart Citation
“…According to [10], who analyzed 2000 seafloor sediment samples at 78 Pacific sites, deep-sea muds show high concentrations of REE (2230 ppm maximum), and could constitute a potential source of these elements in the future. Such high REE concentrations in sediments were not confirmed either by the studies of [21], who studied samples from the central North Pacific, or [16], who examined material collected from the southern part of the Korean claim area (KORDI) of the Clarion-Clipperton Fracture Zone (CCFZ). The former research has shown that total REE contents vary from 418 ppm to 810 ppm, with an average of 532 ppm, while the latter recorded a range from 115 ppm to 1115 ppm, with an even lower average of 490 ppm.…”
Section: Ree In Deep-sea Sedimentsmentioning
confidence: 95%
“…Since the widely cited work of [10], deep-sea sediments have been the subject of numerous studies focused on REE content and resource potential [11][12][13][14][15][16][17][18][19][20]. According to [10], who analyzed 2000 seafloor sediment samples at 78 Pacific sites, deep-sea muds show high concentrations of REE (2230 ppm maximum), and could constitute a potential source of these elements in the future.…”
Section: Ree In Deep-sea Sedimentsmentioning
confidence: 99%
“…The increasing demand for clean energies technologies applied in the permanent magnets and phosphor industries means that REEs such as Nd, Pr and Dy (for permanent magnets) are critical in the international markets, leading to very high prices. The so-called light REEs, such as La and Ce, have broad use as abrasive constituents and naturally have lower prices than HREEs [7,8].…”
Section: Methodsmentioning
confidence: 99%
“…Except for primary metals, rare earth elements are often found in seafloor materials [111,112], enhancing their economic value. However, it is critical to separate REE from base metals, and this might be achieved by SX.…”
Section: Downstream Processingmentioning
confidence: 99%